An exploratory study of core self-evaluation and entrepreneurial motivation. Issue 1 (2nd January 2019) - Crawford, Alleah
ABSTRACT: This research focused on the relationship between core self-evaluation, job satisfaction, and exhaustion that has been supported in the literature. More specifically, this study explored a potential mediation of this relationship by entrepreneurial motivation. The sample included 102 bed and breakfast entrepreneurs. Findings indicate that entrepreneurial motivation partially mediates the core self-evaluation and job satisfaction relationship while it has no mediating effect on the core self-evaluation and exhaustion relationship. Implications and future research are discussed.